PkM-KDUPIP: SOSIALISASI OLAHRAGA SKI AIR DAN WAKEBOARD KEPADA MASYARAKAT DI PROVINSI DKI JAKARTA - Uzizatun Maslikah; Fahmy Fachrezzy; Iwan Hermawan; Endy Safadilla; Indra Adi Budiman (Yayasan Education and Social Center, 2022)
Water Ski and Wakeboard are new sports that are not widely known by many people, especially people in the North Jakarta area. Socialization continues to be carried out to introduce the sport of Water Ski and Wakeboard. The sports community is one of the goals in introducing this sport, as one of the spearheads that will introduce new sports to the community. It is hoped that the community can cultivate sports that can get to know the sport of Water Ski and can become athletes who come here and excel in the sports of Water Ski and Wakeboard. The purpose of this Community Service Program is to socialize the sports of Water Ski and Wakeboard which are still not popular in the community. The method of implementing the activity is the method of instructors from the DKI Jakarta PSAWI Provincial Government who have qualifications in the field of Water Ski and Wakeboard sports which are already nationally licensed. This service activity was held on August 20 and 21, 2022 at Sunter Lake, Jakarta. While the material provided in the implementation of community service consists of 1) Providing practical material: Water Ski and Wakeboard skills and jury practice; 2) Carrying out evaluations in practice. The objectives of this activity are 1) As an effort to increase the knowledge, understanding, and skills of sports students regarding the games and rules of Water Ski and Wakeboard; 2) as an effort to improve the quality and human resources, especially in the Sunter Community to further develop new sports, especially games and regulations Water Ski and Wakeboard